Improving Grade 8 Struggling Readers’ Reading Comprehension Skills through Game-based Learning and Teacher-directed Instruction - Durano, Ernest Gerard B.; Candilas, Kurt S. (BRU ELT JOURNAL, 2023)
The ability to comprehend written material is critical for individuals as it empowers them to accurately interpret and evaluate it, so it is important to facilitate the development of this skill among the learners. The purpose of this research was to determine the effectiveness of Game-Based Learning and Teacher-Directed Instruction in improving the reading comprehension skills of the eighth-grader Struggling readers in a public school in Kinoguitan, Misamis Oriental, Philippines. This study utilized the quasi-experimental design with the use of the teacher-made questionnaire to evaluate the reading comprehension levels of both groups prior to and subsequent to the interventions. Descriptive statistics were used to present results, T-test for paired samples was used to determine significant differences in the two groups, and the T-test for independent samples was used to determine significant differences in the two groups’ reading comprehension increments. The findings demonstrate that Game-Based Learning is more effective than Teacher-Directed Instruction. In order to effectively enhance reading comprehension, the research suggests that instructional approaches incorporate interactive and engaging activities as well as structured and explicit approaches as this foster active cognitive involvement and reinforce fundamental comprehension strategies.